The Influence of Environmental Attributes on Ciliate Dispersal in Freshwater Ecosystems: A Review - Ramzan, Muhammad; Ahmed, Usama Bin (American Journal of Biology and Natural Sciences, 2025)
Introduction Ciliates serve as keystone microbial regulators in freshwater ecosystems, exerting top-down control over bacterial populations through selective grazing. This predation directly influences organic matter mineralization and nutrient cycling (e.g., accelerating nitrogen turnover via excretion of ammonium). Simultaneously, their position at the base of microbial food webs links bacterial energy to higher trophic levels—supporting zooplankton and fish larvae—while their rapid growth responses to environmental shifts make them critical indicators of ecosystem stability. Their role extends to modulating algal blooms through bacterivory-induced nutrient competition, thereby maintaining water quality and functional resilience against eutrophication.Dispersal governs ciliate metacommunity dynamics by mediating colonization-extinction balances across heterogeneous freshwater habitats. Active dispersal (e.g., chemotactic swimming toward nutrient plumes) enables rapid exploitation of local resource patches, while passive mechanisms—including hydrological drift, wind-borne cyst transport, and phoretic hitchhiking on animal vectors (e.g., waterfowl gut endozoochory or insect-mediated ectozoochory)—facilitate long-distance gene flow and regional biodiversity maintenance. This dual dispersal capacity underpins ecosystem resilience by allowing recolonization after disturbances (e.g., droughts, pollution events), yet its effectiveness is constrained by species-specific traits like cyst durability and motility thresholds.